2012
DOI: 10.1002/jmri.23664
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of total choline/water ratios in mouse U87MG xenograft tumors by 1H‐MRS

Abstract: Purpose: To evaluate the reproducibility of the measurement of the total choline-to-water ratio, and the effect of repositioning the subject between scans, using 1 H-magnetic resonance spectroscopy in a mouse U87MG xenograft model. Materials and Methods:In vivo single-voxel MR spectra at 7T from xenograft tumors were obtained using both a water-suppressed and a nonwater-suppressed pointresolved spectroscopy (PRESS) sequence. Reproducibility of the total choline/water ratio was evaluated under the conditions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 37 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…Other metabolites that are also studied include creatine, inositol, and glucose, N‐acetylaspartate and alanine . Zhu et al reported a correlation in the reduction in peak values of Cho with tumor regression …”
Section: Discussionmentioning
confidence: 99%
“…Other metabolites that are also studied include creatine, inositol, and glucose, N‐acetylaspartate and alanine . Zhu et al reported a correlation in the reduction in peak values of Cho with tumor regression …”
Section: Discussionmentioning
confidence: 99%